A comparison of noise level between intraoral suction, HVE, and aerosol suction during anterior teeth preparation in Pediatric Patients (an in-vitro study on dental mannequin) - Risa Miyarsih; Indra Bramanti; Iwa Sutardjo (Journal of Dentomaxillofacial Science, 2021)
Objective: This study aims to compare the noise level between intraoral suction, HVE, and extraoral suction during anterior tooth preparation in children. B Material and Methods: Noise levels were measured with SPL on manikins, which were separated into four treatment groups, namely saliva ejector, saliva ejector + aerosol suction, HVE, and HVE + aerosol suction. Manikins that were equipped with acrylic teeth were prepared for 3 minutes with a highspeed rotary handpiece, then left to rest for 2 minutes, and the cycle repeated twice for each sample, Results: Descriptive data showed that the noise produced by the suction system is higher than the background noise, with a range varied within 74.7-84.5 decibels. ANOVA test showed a significant difference between the mean noise in the test groups, and Post Hoc LSD showed a significant difference in mean noise in the saliva ejector group against the HVE and HVE + aerosol suction group, and the saliva ejector + aerosol suction group against the HVE and HVE + aerosol suction groups, with p-value <0.05. Conclusion: There is a significant difference in noise level with the additional use of the suction systems during dental treatments, which potentially causes discomfort during pediatric dental care.